Thomas Aquinas, Artificial Intelligence, and AI-Generated Music - Tang, Chee Man Michael (New blackfriars, 2026)
This article explores how AI-generated music challenges traditional theological understandings of creativity, spirituality, and the soul. By engaging the theological traditions of analogy and participation developed by Thomas Aquinas, Thomas de Vio Cajetan, and Francisco Suárez, this article reconsiders whether AI-generated music generates emotions and spiritual significances in listeners and whether it might disclose something meaningful about the nature of divine creativity. Rather than arguing AI music is either a technological innovation or artistic threat, this article suggests various frameworks of analogy, participation, and pneumatology to create a better theological discernment on how divine creativity works through secondary causes within creation. The exploration concludes in proposing a ‘theology of digital transcendence’ – a framework for understanding how computational creativity participates in the broader economy of divine creation.